Applications of Capillary Electrophoresis for the Determination of Cannabinoids in Different Matrices - Nicoleta Mirela Blebea; Gabriel Hancu; Robert Alexandru Vlad; Andreea Pricopie (Molecules, 2023)
Cannabinoids, terpenophenolic chemicals found only in cannabis, are primarily responsible for cannabis pharmacologic effects; nearly 150 distinct cannabinoids have been identified thus far. Among these, the main psychoactive molecule, tetrahydrocannabinol (THC), and the non-psychoactive counterpart, cannabidiol (CBD) are distinguishable. In the past decade, a CBD-containing pharmaceutical preparation was approved by Food and Drug Administration (FDA) for the treatment of drug-resistant epileptic seizures in children, and research trials for a variety of additional medical conditions for which CBD has been suggested as a therapy are being conducted. Additionally, the number of “CBD-containing” dietary supplements, largely available online, is increasing rapidly. Consequently, the necessity for the development of qualitative and quantitative methodologies for the analysis of the bioactive components of Cannabis is rising because of the increase in the production of therapeutic cannabis products. One of the analytical methods with good potential in cannabinoids analysis is capillary electrophoresis (CE). It has advantages related to high separation efficiency, relatively short analysis time, and the small consumption of analytes and reagents which generates relatively lower operational costs than other methods. This review focuses on the use of CE techniques to examine biological matrices and plant materials for the presence of cannabinoids and other bioactive compounds found in cannabis. The advantages, drawbacks, and applicability of the various electromigration approaches are also assessed. The article provides an overview of the “state of the art” and the latest trends in CE-based methods for the determination of cannabinoids.